Dosing of indocyanine-green for intraoperative laser fluorescence angiography in kidney transplantation - Rother, Ulrich; Gerken, Andreas L. H.; Karampinis, Ioannis; Klumpp, Madeline; Regus, Susanne; Meyer, Alexander; Apel, Hendrik; Kraemer, Bernhard K.; Hilgers, Karl Friedrich; Lang, Werner; Nowak, Kai (Microcirculation, 2017)
Sufficient blood supply is a crucial factor determining postoperative allograft function in kidney transplantation. Therefore, besides the surgeon's individual impression a method for evaluating the quality of the organ's microperfusion is required. Laser fluorescence angiography with indocyanine-green (ICG) is an emerging tool for this purpose. However, no reproducible quantification of ICG fluorescence has been performed in transplantation so far.This retrospective two-center study was designed to evaluate the dosing of ICG for intraoperative laser fluorescence angiography in kidney transplantation. The Spy Elite(®) system (NOVADAQ, Canada) was employed for quantitative assessment of allograft microperfusion. ICG was administered systemically 5 min after reperfusion applying doses between 0.25 and 0.01 mg ICG per kg body weight. Quantitative assessment was performed with the implemented SPY-Q Software.57 kidney recipients were included in two centers. The generated curves showing ICG ingress and egress rates were not evaluable due to oversensing when doses exceeded 0.02 mg per kg body weight.Fluorescence angiography with ICG is an emerging tool for the intraoperative quality control and evaluation of microperfusion in kidney transplantation. A dose of 0.02 mg ICG per kg body weight is recommended in order to ensure the quantitative assessment with SPY-Q. This article is protected by copyright. All rights reserved.
EVALuna2:3964